Metagenomic study of the gut microbiota associated with cow milk consumption in Chinese peri-/postmenopausal women - Tian, Bo; Yao, Jia-Heng; Lin, Xu; Lv, Wan-Qiang; Jiang, Lin-Dong; Wang, Zhuo-Qi; Shen, Jie; Xiao, Hong-Mei; Xu, Hanli; Xu, Lu-Lu; Cheng, Xiyu; Shen, Hui; et al. (Frontiers in Microbiology, 2022)
Cow milk consumption (CMC) and alterations of gut bacterial composition are proposed to be closely related to human health and disease. The aim of our research is to investigate the changes in human gut microbial composition in Chinese peri-/postmenopausal women with different CMC habits. A total of 517 subjects were recruited and questionnaires about their CMC status were collected. 394 subjects were included in the final analyses. Fecal samples were used for studying gut bacterial composition. All the subjects were divided into a control group (n=248) and a CMC group (n=146) according to their CMC status. Non-parametric test and LEFSe at different taxonomic levels were used to reveal differentially abundant taxa and functional categories across different CMC groups. Relative abundance (RA) of one phylum (p_Actinobacteria), three genera (g_Bifidobacterium, g_Anaerostipes and g_Bacteroides) and 28 species diversified significantly across groups. Specifically, taxa g_Anaerostipes (p<0.01), g_Bacteroides (p<0.05), s_Anaerostipes_hadrus (p<0.01) and s_Bifidobacterium_pseudocatenulatum (p<0.01) were positively correlated with CMC levels, but p_Actinobacteria (p<0.01) and g_Bifidobacterium (p<0.01) were negatively associated with CMC levels. KEGG module analysis revealed 48 gut microbiome functional modules significantly (p<0.05) associated with CMC, including Vibrio cholerae pathogenicity signature, cholera toxins (p=9.52e-04), cephamycin C biosynthesis module (p=0.0057), among others. In conclusion, CMC was associated with changes in gut microbiome patterns including beta-diversity and richness of some gut microbiota. The alterations of certain bacteria including g_Anaerostipes, s_Bifidobacterium_pseudocatenulatum in CMC group should be important for human health. This study further supports the biological value of habitual cow’s milk consumption.